THE IMPACT OF STRATEGIC CAPABILITIES IN ENHANCING THE QUALITY OF SERVICES - Sarah Ghaleb Fahmy Al-Tikriti; Mr. Dr. Khaled Kamal Al-Din (Scholars Digest Publishing, 2023)
The study aims to understand the relationship between strategic capability and the quality of services in its dimensions, determine the impact of this capability in addressing the quality of service, and understand the extent to which individual data expressed by gender, age, educational level, length of service and place of work influence this relationship, and the extent of its application at Al-Rafidain Bank, Salah al-Din Governorate. / Iraq Branch. The list of research adopted the descriptive approach to analysis in studying reality, and through this method, data was collected through a questionnaire, consisting of (40) items, and the significance of its validity and reliability was verified, as the reliability coefficient of the questionnaire items was determined (93%). The research population included all employees employed at Rafidain Bank, and their number reached 160 individuals in all branches and departments. The questionnaire was the research tool, and it was distributed to more than (100) individuals in a manner appropriate to the number of employees in all branches and departments, and it was filtered to obtain (100) a valid sample. Search . The research produced several results, the most important of which are: 1- The results showed consistency with the first hypothesis, but the results showed that the index level of the strategic capability dimension and improvement in service efficiency was positive, which indicates a direct correlation between them and the degree of correlation coefficient reaches (0.700). 2- The summary of measuring the second assumption showed that increasing (strategic capabilities) by one unit leads to an increase (quality of services) by (909%). The most important recommendations of the study are the following: 1- The need to increase senior management’s awareness of the importance of paying attention to the organization’s planning capabilities and developing them, and identifying the impact that these capabilities play in improving the organization’s competitive ability and achieving its goals. 2- The need for the bank management to respond quickly and meet customer requests because these are characteristics that influence the type of banking services, by understanding their needs and desires for customers and quickly completing the banking service while paying attention to customers’ complaints and solving their problems.
Keywords: strategic capability, enhancement, quality of services, the bank.